2021
DOI: 10.24938/kutfd.970072
|View full text |Cite
|
Sign up to set email alerts
|

Acil Serviste Çocuklarda Düşme Olgularının Yönetimi: 261 Çocuk Olgunun Analizi

Abstract: Objective: Pediatric falls cause a significant burden for emergency departments and have negative patient outcomes such as prolonged length of stay and increased costs. The objective of this study was to evaluate results of the management of pediatric fall cases in an emergency department.Material and Methods: Pediatric patients who presented to our emergency department due to falling injury were evaluated and analyzed according to the demographic data, including age and gender, Glasgow Coma Scale, Injury Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The ISS values were seen to be considerably higher in cases of multiple trauma in child victims wounded as a consequence of a falling [18]. In this study, the ISS and NISS values were significantly higher in multiple traumas than in head and neck injury, extremity injury, and chest injury.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…The ISS values were seen to be considerably higher in cases of multiple trauma in child victims wounded as a consequence of a falling [18]. In this study, the ISS and NISS values were significantly higher in multiple traumas than in head and neck injury, extremity injury, and chest injury.…”
Section: Discussionmentioning
confidence: 44%
“…Children under the age of 16 years with a head or chest injury had a higher risk of death compared to children with other injuries [8]. Demirel and Akpınar reported that in children injured as a result of falling, the most common injuries were to the head and neck (49%) and extremities (39%) [18]. The extremities (45.10%) and head-neck area (34.80%) were the most prevalent injuries in children under the age of 15 years in traffic accidents, according to Serinken and Zen [16].…”
Section: Discussionmentioning
confidence: 99%